Assessment of knowledge of community health workers and mothers on infant and young child feeding and practices of mothers - Chowdhury, Anita Sharif; Islam, Qazi Shafayetul; Roy, Sanjit (BRAC Research and Evaluation Division (RED), 2019)
Poor infant feeding practices are some of major causes of under-nutrition in children under five years of age in Bangladesh. In order to address the issue, BRAC ·has implemented the Alive and Thrive (A&T) programme to promote adequate infant and young child feeding (IYCF) practices in rural Bangladesh. The programme had already been in operation in 22 upazilas in nine districts for more than one-and a half years before the time of the survey (October 2011). We tried to understand the level of knowledge and practices of mothers in IYCF in A& T programme areas. In addition, the study also investigated the Shashthya Shebikas' (SS) (health volunteer) knowledge of IYCF. The study was a post-test cross-sectional study to compare areas with and without A & T intervention as no baseline data was available. Both structured and semi-structured tools were used to collect information. The respondents were: women with children aged under one year (n=1 ,224) and SSs (n=120). Findings reveal that both mothers and SSs had reasonably good knowledge of breast-feeding. For example, 95% of mothers knew about colostrum feeding and the duration of exclusive breast-feeding (without water). Breast-feeding practice was commendable as 89% of mothers fed colostrum immediately after birth, moreover, 75% of mothers practised exclusive breast-feeding. Gapes in knowledge were found regarding the types as well as the nature of complementary food among both mothers and SSs. For example, gaps in knowledge existed in offering age appropriate food, in the frequency of serving and in the quantity to be served to children under one year. In conclusion, it can be said that A& T had progressed well in terms of some important IYCF indicators such as breast-feeding practices. However, it more effort needs to be given to improve complementary feeding practices.